Importance of CLT Principles in Teaching Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article focuses on the deep understanding of CLT in the field of English Language Teaching in Uzbekistan context. The main purpose of the article is to guide language teachers in learning the principles of CLT and to provide possible ways of applying them in teaching.